IDENTIFIKASI CACING PARASIT DAN PREVALENSINYA PADA TERNAK KAMBING DI KELURAHAN KOYA BARAT, DISTRIK MUARA TAMI, KOTA JAYAPURA, PROVINSI PAPUA - Apriani Herni Rophi (Universitas Cenderawasih, 2015)
ABSTRACTThe purpose of this study was to determine the types of worms parasite and levels of their prevalence that infect goats in West Koya Village, Muara Tami District, Jayapura City, Papua Province. To determine the type of the worms, it should be done the fecal examination by sedimentation method Formalin-Ether. To determine the type of the worms, it should be done the fecal examination by sedimentation method Formalin-Ether. The prevalence of species parasitic worms that infected goats in West Koya village is Mecisticirrus with the number of samples infected as many as 50 samples (62.5%), Oesophagostomum radiatum infect 27 samples (33.75%), Trichuris discolor infect 10 samples (12.5%) and Paramphistomum cervi infect 8 samples (10%).Keywords: prevalence, types of parasitic worms,.